A novel method of methanol concentration control through feedback of the amplitudes of output voltage fluctuations for direct methanol fuel cells. (1st April 2016) - An, Myung-Gi; Mehmood, Asad; Hwang, Jinyeon; Ha, Heung Yong
Abstract: This study proposes a novel method for controlling the methanol concentration without using methanol sensors for DMFC (direct methanol fuel cell) systems that have a recycling methanol-feed loop. This method utilizes the amplitudes of output voltage fluctuations of DMFC as a feedback parameter to control the methanol concentration. The relationship between the methanol concentrations and the amplitudes of output voltage fluctuations is correlated under various operating conditions and, based on the experimental correlations, an algorithm to control the methanol concentration with no sensor is established. Feasibility tests of the algorithm have been conducted under various operating conditions including varying ambient temperature with a 200 W-class DMFC system. It is demonstrated that the sensor-less controller is able to control the methanol-feed concentration precisely and to run the DMFC systems more energy-efficiently as compared with other control systems. Highlights: A new sensor-less algorithm is proposed to control the methanol concentration without using a sensor. The algorithm utilizes the voltage fluctuations of DMFC as a feedback parameter to control the methanol feed concentration. A 200 W DMFC system is operated to evaluate the validity of the sensor-less algorithm. The algorithm successfully controls the methanol feed concentration within a small error bound.